Effect of Nd: YAG laser irradiation and Mechanical force on cultured human osteoblasts. - Tsuka, Yuji; Kunimatsu, Ryo; Gunji, Hidemi; Abe, Takaharu; Concepción Medina, Cynthia; Nakajima, Kengo; Kimura, Aya; Hiraki, Tomoka; Nakatani, Ayaka; Tanimoto, Kotaro (Journal of Lasers in Medical Sciences, 2020)
Background: In recent years, laser irradiation in the NIR (Near infrared ray) area has been reported to promote bone healing. There are also reports that laser irradiation accelerates orthodontic tooth movement. In this study, we investigated the effect of NIR laser irradiation and mechanical stimulation on osteoblasts. Methods: We seeded osteoblast-like cells and laser irradiation was performed 24 hours after cell seeding. In addition, a control group not performing anything, a group performing only neodymium · doped (Nd): YAG laser irradiation, a group performing only centrifugal loading, and a group using both Nd: YAG laser irradiation and centrifugal force loading were set, and after 24 hours and after 48 hours, cells were collected and Quantitative real-time PCR was performed. Results: At 24 hours after laser irradiation, gene expression of Alkaline Phosphatase (ALP), Receptor activator of NF-κB ligand (RANKL) and Osteoprotegerin (OPG) was significantly higher in the 2.0 w group than in the control group. In addition, the RANKL / OPG ratio was higher in the 2.0 w group than in the control group. Also, in the group using laser irradiation and centrifugal load in combination 24 hours after laser irradiation, ALP and OPG showed significantly higher values than those with centrifugal load only group. Furthermore, the RANKL / OPG ratio also showed high values. Conclusion: These results suggest that osteoblast-like cells activate genes related to bone metabolism by combining mechanical stimulation and laser irradiation. This helps to elucidate the influence of laser irradiation during tooth movement.